Effect of anti-retroviral therapy on oxidative stress in hospitalized HIV-infected adults with and without TB - Musisi, Emmanuel; Matovu, Denis K.; Bukenya, Andrew; Kaswabuli, Sylvia; Zawedde, Josephine; Andama, Alfred; Byanyima, Patrick; Sanyu, Ingvar; Sessolo, Abdul; Seremba, Emmanuel; Davis, Lucian J.; Worodria, William; et al. (African health sciences, 2018)
HIV infection and opportunistic infections cause oxidative stress (OS), which is associated with tissue damage. Anti-retroviral therapy (ART) is used to treat HIV and decrease the risk of opportunistic infections, but it is unclear whether ART reduces OS. Association of ART with OS was investigated. Methods: We stratified a convenience sample of frozen serum or plasma from HIV-infected, ART-naïve (n= 21); HIV-infected, ART-treated (n= 14); HIV and PTB co-infected, ART-naïve (n= 21); HIV and PTB co-infected, ART-treated (n= 25) patients. Controls (n= 21) were HIV-negative adults without TB symptoms. Concentration of OS markers namely: transaminases (ALT and AST), gamma glutamyl transpeptidase (GGT), albumin, total protein, malondialdehyde (MDA), vitamin C, and total anti-oxidant status (TAS) were determined. Results: AST (p< 0.001), GGT (p< 0.001), total protein (p= 0.001) and MDA (p< 0.001) were higher in HIV patients compared to controls. Vitamin C (P< 0.0001) and albumin (p< 0.01) were lower in HIV-patients relative to controls. ART was only associated with higher albumin (p= 0.001), higher GGT (p= 0.02) and lower vitamin C (p= 0.009). HIV and PTB co-infection was only significantly associated with higher GGT (p= 0.01) and AST (p= 0.03). Conclusion: We identified severe OS among HIV-patients. ART was associated with both increased and reduced markers of OS hence suggesting that ART may not attenuate OS.